Pelatihan Tata Rias Dan Busana Dalam Meningkatkan Kreativitas Para Guru Dalam Musyawarah Guru Mata Pelajaran (MGMP) Kesenian Daerah Di Karanganyar - Tubagus Mulyadi (Abdi Seni, 2016)
Service for Society is one of the duty that have to be done by a lecturer. The dance department gave this opportunity to the lecturers to make some links to do the Tri Dharma Higher Education, which one of it called Pengabdian Kepada Masyarakat (PPM). The lecturers did this in a work with the relationship between theDance department of ISI Surakarta and the arts teachers in the Kabupaten Karanganyar area. This work wanted to give the teachers how to develope their knowledge andÂ their competence trough the improving skill, and creativity, related with skill of traditional make up, fantasy make up, dan how to wear costumes in the performance. Trough the teaching prosess and apresiation, for the teacher will be able to use this for the educational work in their class. This work also became a part of pubication for ISI Surakarta. The methode for this work is lecture demonstration. The training of make up and costume is really use full for the participants. Key words : skill, PPM, make up and costume